Settlement of a Pile Foundation Considering Linear and Rheological Properties of Soils - Armen Z. Ter-Martirosyan; Lyubov Yu. Ermoshina; George O. Anzhelo (Buildings)
Despite numerous studies of single piles and practical experience with their application, methods for calculating settlements of pile foundations remain limited. The existing objective need for specialized methods of pile foundation settlement calculation that take into account the rheological properties of the base soils is becoming more and more important, especially in the construction of unique objects in complex ground conditions. When predicting the stress–strain state of the pile–raft-surrounding soil mass system, it is allowed to consider not the entire pile foundation as a whole, but only a part of it—the computational cell. In the present work, we have solved the problems of determining the strains of the computational cell consisting of the pile, the raft and the surrounding soil according to the column pile scheme and hanging pile scheme, on the basis of the Kelvin–Voigt rheological model, which is a model of a viscoelastic body consisting of parallel connected elements: Hooke’s elastic spring and Newtonian fluid. According to our results, we obtained graphs of the dependence of strains of the computational cell on time at different pile spacing and different values of coefficients of viscosity of the surrounding soil, and a formula for calculating the reduced modulus of deformation of the pile. The results of the present study can significantly improve the accuracy of calculations during construction on clayey soils with pronounced rheological properties and, as a result, increase the reliability of pile structures in general.